Effect of sintering temperature on properties of Li0.5Fe2.5O4 ferrites nanoparticles - N., T. Lan; N., P. Duong; T., D. Hien; L., N. Anh (JST: Engineering And Technology For Sustainable Development, 2022)
In this work, Li0.5Fe2.5O4 ferrite nanoparticles were synthesized by the sol-gel method. The influence of the annealing temperature on phase formation, microstructure, and magnetic characterizations of Li-ferrite was explored. The result of XRD showed that the preliminary calcined and sintered samples at 500oC are single-phase spinel structures. The crystallite size increases from 16.9 nm to 37.8 nm, with sintering temperatures increasing from 500oC to 800oC. The magnetic properties of Li ferrite powders were strongly depended on sintering temperature (Ttk). Coercive force (HC) followed a simple model of Gauss's law. The magnetic saturation (MS) was dependent on the sintering temperature of the gel, reaching a maximum value of 74 emul/g, which is higher than the bulk material. Curie temperature (TC) of Li ferrite nanoparticles is a function of gel sintering temperature, and it reaches 98% of the TC value of bulk materials.